Development of the Reed Industry Group Through Training in Financial Management, Management and Sustainable Architectural Building Design - DEWI, Kadek Goldina Puteri; WAHYUNI, Ni Made; ARTHA, Pande Putu Dwi Novigga (Akuntansi dan Humaniora: Jurnal Pengabdian Masyarakat, 2024)
Industry plays a vital role in reducing poverty in developing countries. In Bali, the creative industry has developed rapidly, although initially, it was still small. The alang-alang roofing industry, which focuses on producing and using roofing from alang-alang leaves, is a significant sector in the construction and property development industry. This material is used in traditional buildings and modern, environmentally friendly building designs. A case study of the "Tegal Wangi" thatched roof industry in Lodtunduh Village, Ubud, shows that financial management and risk management are essential for the success of small and medium enterprises (SMEs). Financial education through simple bookkeeping is essential to provide in-depth understanding for business owners and managers. In addition, risks in this industry include competition, changes in customer demand and quality, and fluctuations in raw material prices. Solutions like product diversification and flexible marketing strategies can help manage these risks. Sustainable architectural building design is also a crucial factor. Collaboration between architects and industrial owners can create functional, aesthetic buildings resistant to extreme weather. Using sustainably sourced reeds and following environmentally friendly farming practices are essential steps in maintaining the balance of the ecosystem.